Information and communication technologies in education, research, and industrial applications : 11th International Conference, ICTERI 2015, Lviv, Ukraine, May 14-16, 2015, Revised Selected Papers /: 11th International Conference, ICTERI 2015, Lviv, Ukraine, May 14-16, 2015, Revised Selected Papers. (2016) - Unknown
No abstract available